Selected determinants and sequelae of exclusive breastfeeding of up to six months in infants attending hospital and field well baby clinics - Bandusena, A.S.L (My University, 2003)
The exclusive breastfeeding rate of four months and beyond was 52.1 ,with only 3.6 being exclusively breastfed for five months and none for six. The factors that favoured exclusive breastfeeding of the earlier child for four or more months, a grater number of antenatal clinic visits, hearing about the optimal duration of exclusive breastfeeding via the media, being well-instructed on expressed milk and surprisingly, delivery by caesarean section. There was no significant relationship between maternal employment, time of first breastfeed, incidence of diarrhoea and the duration of exclusive breast feeding. Between the duration of exclusive breast feeding and the incidence of respiratory tract or diarrhoeal infections